iPad Management and Its Impact on Students’ Motivation and Achievement at SIS Palembang - Arifin, Muhammad Nabil; Widayatsih, Tri; Nurlina, Nurlina (Journal of Social Work and Science Education, 2025)
This study aims to investigate the management of iPad integration in enhancing student motivation and academic achievement at Singapore International School (SIS) Palembang. Specifically, it examines (1) how iPad use is managed to boost motivation, (2) its impact on academic performance, and (3) the challenges and solutions in its implementation. Using a qualitative descriptive method, data were collected through interviews, observations, and documentation involving teachers, students, and school administrators. The results reveal that iPad management follows a systematic cycle: planning (school policies and teacher training), organizing (structured role distribution), implementing (active, technology-driven lessons), and evaluating (digital assessments and stakeholder feedback). The findings demonstrate that iPads significantly increase student motivation by fostering engagement, collaboration, and personalized learning, while also improving academic outcomes through enhanced 21st-century skills. Key challenges include screen time concerns, device dependency, and technical issues. The study’s novelty lies in its holistic analysis of iPad management within a Southeast Asian international school context, bridging gaps between policy, pedagogy, and practical barriers. Practical implications highlight the need for adaptive policies, ongoing teacher training, and robust evaluation frameworks to optimize technology integration. This research contributes to the discourse on digital education by providing a replicable model for balancing technological innovation with sustainable educational practices.